Peluang Kompetensi Clinical Engineering untuk Meningkatkan Prospek Kerja Lulusan Program Studi Teknik Biomedik di Indonesia - Ahmad Fathir Rahman; Basari Basari (Jurnal Pendidikan Indonesia, 2025)
In Indonesia, the clinical engineering sector is crucial for advancing healthcare services, yet the integration of university curricula with industry demands remains suboptimal. This mismatch between educational offerings and market needs has significant implications for graduate employability and the quality of healthcare services. This study aims to critically evaluate how well academic programs in clinical engineering align with the evolving needs of Indonesia’s healthcare industry and to enhance employment opportunities for graduates. Employing thematic analysis based on Clarke & Braun's model and drawing on purposive sampling, interviews were conducted with stakeholders across the biomedical field, including educators, industry professionals, and healthcare providers. This approach allowed for a deep dive into the existing gaps between educational content and industry expectations. The research highlights a substantial lack of practical training and insufficient collaboration between academic institutions and the healthcare industry. These factors contribute to the skill mismatch among graduates and underscore the need for curriculum adjustments. Key findings suggest that integrating practical skills training and enhancing industry-academic partnerships are critical steps towards improving graduate employability. The study suggests that strategic curriculum adjustments are needed to better prepare graduates for the workforce.